a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,一道数学题,a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,打不出根号,请谅解,求快!

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/03 19:34:25
a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,一道数学题,a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,打不出根号,请谅解,求快!
x)KTS64N|ڿD{:m$]cMnPV(1IɎMtfPnOv>my~ //yՊ6IE4p9%|;@g^,ZtOói;xc˹^lr̾`U@Ku.5Pb@I`ޓ]}f:f!mr2 R2D$M@Y[2B2P\ 1]ɼ

a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,一道数学题,a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,打不出根号,请谅解,求快!
a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,一道数学题,
a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,打不出根号,请谅解,求快!

a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,一道数学题,a²+b²+根号(a-c)=根号(b-3)+根号(3-b)-2ab,打不出根号,请谅解,求快!
根据被开方数为非负数得
b-3≥0 3-b≥0
解得b=3
于是
a²+b²+√(a-c)=0-2ab
a²+2ab+b²+√(a-c)=0
(a+b)²+√(a-c)=0
a+b=0 a-c=0 b=3
解得
a=-3 c=3